Chemosensing Ensembles for Monitoring Biomembrane Transport in Real Time1. Issue 10 (27th January 2014) - Ghale, Garima; Lanctôt, Adrienne G.; Kreissl, Hannah T.; Jacob, Maik H.; Weingart, Helge; Winterhalter, Mathias; Nau, Werner M.
Abstract The efficacy of drugs and biomolecules relies on their ability to pass through the bilayer. The development of methods to directly and sensitively monitor these membrane transport processes has remained an experimental challenge. A macrocyclic host (p‐sulfonatocalix[4]arene or cucurbit[7]uril) and a fluorescent dye (lucigenin or berberine) are encapsulated as a chemosensing ensemble inside liposomes, which allows for a direct, real‐time fluorescence monitoring of the passage of unlabeled bioorganic analytes. This in vitro assay is transferable to different channel proteins and analytes, has potential for fluorescence‐based screening, e.g., of channel modulators, and yields the absolute kinetics of translocation. Using this new biophysical method, we observed for the first time direct rapid translocation of protamine, an antimicrobial peptide, through the bacterial transmembrane protein OmpF.